Comparative metabolomics reveals biogenesis of ascarosides, a modular library of small-molecule signals in C. elegans. - Von Reuss, Stephan; Bose, Neelanjan; Srinivasan, Jagan; Yim, Joshua J; Judkins, Joshua C; Sternberg, Paul W; Schroeder, Frank C (My University, 2012)
In the model organism Caenorhabditis elegans, a family of endogenous small molecules, the ascarosides function as key regulators of developmental timing and behavior that act upstream of conserved signaling pathways. The ascarosides are based on the dideoxysugar ascarylose, which is linked to fatty-acid-like side chains of varying lengths derived from peroxisomal β-oxidation. Despite the importance of ascarosides for many aspects of C. elegans biology, knowledge of their structures, biosynthesis, and homeostasis remains incomplete. We used an MS/MS-based screen to profile ascarosides in C. elegans wild-type and mutant metabolomes, which revealed a much greater structural diversity of ascaroside derivatives than previously reported. Comparison of the metabolomes from wild-type and a series of peroxisomal β-oxidation mutants showed that the enoyl CoA-hydratase MAOC-1 serves an important role in ascaroside biosynthesis and clarified the functions of two other enzymes, ACOX-1 and DHS-28. We show that, following peroxisomal β-oxidation, the ascarosides are selectively derivatized with moieties of varied biogenetic origin and that such modifications can dramatically affect biological activity, producing signaling molecules active at low femtomolar concentrations. Based on these results, the ascarosides appear as a modular library of small-molecule signals, integrating building blocks from three major metabolic pathways: carbohydrate metabolism, peroxisomal β-oxidation of fatty acids, and amino acid catabolism. Our screen further demonstrates that ascaroside biosynthesis is directly affected by nutritional status and that excretion of the final products is highly selective.